Emotional Intelligence, Intellectual Intelligence, and Competence on Work Commitment Through Employee Job Satisfaction in Companies Engaged in Plastic Manufacturing: Kecerdasan Emosional, Kecerdasan Intelektual, dan Kompetensi Terhadap Komitmen Kerja Melalui Kepuasan Kerja Karyawan di Perusahaan yang Bergerak di Bidang Manufacture Plastik - Raharjo, Muhammad Deni Tri; Abadiyah, Rifdah (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the effect of emotional intelligence, intellectual intelligence and competence on work commitment through employee job satisfaction at PT Santoso Jawi Abadi. This study uses quantitative research with hypothesis testing. The sample used in this study were 100 employees at PT Santoso Jawi Abadi. The analytical tool used in this study uses SPSS statistical software version 25.0. The main data in this study came from questionnaires. The results of this study prove that (1) there is a direct influence of emotional intelligence (X1) on job satisfaction (M) on employees, (2) there is a direct influence of intellectual intelligence (X2) on job satisfaction (M) on employees (3) there is a direct influence of competence (X3) on job satisfaction (M) on employees, (4) there is a direct effect of job satisfaction (M) on work commitment (Y), (5) emotional intelligence, intellectual intelligence, competence and job satisfaction have an effect on directly on work commitment, (6) indirectly emotional intelligence (X1) through job satisfaction (M) has a significant effect on work commitment (Y), the value of direct influence is smaller than the value of indirect influence, (7) indirectly intellectual intelligence (X2) through job satisfaction (M) has a significant effect on work commitment (Y) because the value of direct influence is smaller than the value of indirect influence, (8) indirectly competence (X3) through job satisfaction (M) has a significant effect on work commitment (Y) because the value of the indirect effect is greater than the value of the direct influence.